Pengaruh Intellectual Capital, Growth Opportunity dan Cash Holding Terhadap Nilai Perusahaan - Leny Suzan; Mentari Utami Supriyadiputri (Universitas Muhammadiyah Malang, 2023)
Purpose: Firm value is a shareholder perception resulting from the company’s performance during the course of business. One of the impressions resulting from the worth of the firm is the value of the stock price. In line with the phenomenon raised regarding the share prices of Indonesia pulp and paper companies listed on Indonesia Stock Excharge and pulp and paper companies in Asia, this is certainly a phenomenon that is used a study. The purpose of this study is to ascertain how Intellectual Capital, Growth Opportunity, and Cash Holding have simultaneous and partial effects on Firm Value. Methodology/approach: This study used quantitative methods. The research sample technique used purposive sampling which resulted in 7 pulp and paper companies conducting an Intial Public Offering (IPO) on the Indonesia Stock Excharge with a period of five years. The e-views statistical processing program version 12.0 was utilized to support the regression analysis of panel data used in this study. Findings: The results showed that intellectual capital, growth opportunity, and cash holding had an influence on the firm value simultaneously by 98.20%. Partially, growth opportunity shows that there is an influence on the firm value. While financial holdings and intellectual capital have little impact on the firm's worth. Practical and Theoretical contribution/Originality: This research contributes to the reader with the novelty of variables and theories used by researches, thus adding broader insight. Research Limitation: Based on the findings obtained, there are limitations in this study, namely intellectual capital measured by the VAIC™ indicator and cash holding measured by the CASH indicator cannot be used as an illustration of how to archieve good firm value, the object of research only uses pulp and paper companies that conduct IPOs on the Indonesia Stock Excharge.